Návrh změn informačního systému firmy Eisberg, a.s. - Sichler, Marek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Moje práce se zabývá návrhem změn informačního systému firmy EISBERG, a.s. Na základě získaných informací navrhnu, který modul systému je potřeba rozšířit, popřípadě předložím návrh na reorganizaci postupu a úkonu v informačním systému.

The object of this bachelor´s thesis is to analyze current status of information system of company EISBERG, a.s. As a result of this analysis will by propsal of system procedure reorganization and expansion.
Review of the information system of company Eisberg,
Keywords: Informační systém; bezpečnost IS; hardware; softwarem; orgware; peopleware; dataware; customers; supplies; management IS; Information system; security of IS; hardware; softwarem; orgware; peopleware; dataware; customers; supplies; management IS